2012
DOI: 10.1002/pen.23343
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of copolymer grafted magnetic nanoparticles via surface‐initiated nitroxide‐mediated radical polymerization

Abstract: “Grafting from” surface‐initiated nitroxide‐mediated radical polymerization (SI‐NMRP) techniques were used to synthesize poly[styrene‐co‐(maleic anhydride)] copolymer brushes from the Fe3O4 surfaces. Well‐defined polymer chains were grown from the Fe3O4 surfaces to yield particles with a Fe3O4 core and a polymer outer layer. The observed narrow molecular weight distributions (Mw/Mn), linear kinetic plots and linear plots of molecular weight (Mn) versus conversion for the free polymer indicated that the chain g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…It was incorporated onto Fe 3 O 4 [18] and silica,[16] with both of these particles being subsequently reacted with styrene and maleic anhydride to produce a core inorganic nanoparticle with polymer chains extending from it. Therefore, these publications suggest that graphite oxide used under the conditions presented in this report could be oxidized to contain peroxides, aldehydes and ketones, as well as to the attachment of TEMPO to the surface of the starting material, as shown Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was incorporated onto Fe 3 O 4 [18] and silica,[16] with both of these particles being subsequently reacted with styrene and maleic anhydride to produce a core inorganic nanoparticle with polymer chains extending from it. Therefore, these publications suggest that graphite oxide used under the conditions presented in this report could be oxidized to contain peroxides, aldehydes and ketones, as well as to the attachment of TEMPO to the surface of the starting material, as shown Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…[15] In addition to these reactions, we have found that silanol groups (Si-OH) present on the surface of silica dioxide[16] or at the ends of hydroxyl-terminated polymers[17] can be chemically modified with TEMPO groups using OS, promoting a functionalization reaction instead of an oxidation. Recently, Chen et al [18] applied this strategy to functionalize magnetite nanoparticles with TEMPO moieties. To the best of our knowledge, OS have not been studied as intercalating agents to functionalize and exfoliate the groups present on the surface and edges of GO.…”
Section: Introductionmentioning
confidence: 99%
“…Thermogravimetric Analysis. Thermogravimetric results were obtained with a TG209 F3 system (Netzsch, Germany) within the temperature range 50-850 C at a heating-up rate of 10 C min 21 . A sample weight of about 4 mg was used for all the measurements, and nitrogen was used as the purging gas at a flow rate of 50 mL/min.…”
Section: Characterizationmentioning
confidence: 99%
“…2. The absorption peak at about 3550 cm 21 for ATP is attributed to hydroxyl groups related to association Si-OH and absorption water in nano-tunnels, and the two sharp peaks at 1029 cm 21 and 982 cm 21 correspond to bending and stretching vibration of Si-O-Si. The peak at 1654 cm 21 is caused by bending vibration of zeolite water.…”
Section: Ftir Measurementmentioning
confidence: 99%
“…Controlled/radical polymerization methods are commonly used since the molecular weight of synthesized polymers increases linearly with the reaction time, providing copolymers with narrow distribution since transfer and termination reactions are significantly reduced [14,15]. Therefore using atom transfer radical polymerization ATRP [16e19], reverse addition fragmentation chain transfer polymerization RAFT [20,21], or in some cases nitroxide mediated polymerization NMP [22,23] one can design very precisely the composition of the final hybrid particles. ATRP is one of the most often frequently used techniques for the synthesis of such coreeshell materials.…”
Section: Introductionmentioning
confidence: 99%